Subacute Combined Spinal Cord Degeneration by Recreational Laughing Gas (N2O) Use. (March 2019) - Onrust, Marthe R; Frequin, Stephan TFM
Background: A few young patients were brought in with subacute combined spinal cord degeneration at the Department of Neurology in our hospital. They all have used laughing gas for recreational purposes. Case: A 30-year-old woman, known with alcohol abuse, was presented to our Department of Neurology for having paresthesia and unstable movements of arms, legs, and trunk for 9 days. She has used 50 laughing gas patterns per day. The diagnosis of laughing gas–induced combined spinal cord degeneration was evident by the low count of vitamin B12 combined with lesions shown on magnetic resonance imaging (MRI). Abstaining from the laughing gas, weekly intramuscular injections of hydroxocobalamin and revalidation, she was fully recovered in 8 weeks. Conclusions: Recreational use of laughing gas seems to be more used in our society, however, without having any knowledge of the neurological consequences. The right diagnosis and treatment can provide full recovery in these patients. Furthermore, attention for this diagnosis can help increase social awareness.